الوقف والابتداء في القرآن الكريم والاستفادة منهما في تعليم اللغة العرية في سورة ق نموذجا - QUDWATUN HISAN (Rayah Al-Islam, 2019)
Al Waqfu and al Ibtida’ is one of important part an Arabic languistic principle that every student of Arabic language have to understand clearly. Al Waqfu wa al Ibtida’ is a principle that arrange how to stop how to begin when reading sentences. This principle is guidience that assure the student of Arabic language catching the true meaning of the Arabic text that she or he reads, especially the Qur’an text. The implemementation of this principles may lead to missunderstanding the true meaning of a text. The implementation of this principle not only critical for the reader its also critical for the listener, they also could missunderstand the meaning of the text that they hear.The aim of this study is to analyse the methods that used by the islamic scholars to build the principle, especially tht related to the Qur’anic text. Second, this study will disscus the benefit of implementation of this principle in Arabic language study. This research is based on library research and discriptive analysis.The study several that Al-Waqaf is catagorized to four category that is; perfect stop, sufficent stop, good stop, and bad stop. Al- Ibtida’ is categorized to two category that is; good begining, and bad beging in Arabic language studies this knowladge could be use as parameter to evaluate the capacibility of a student in understanding the true meaning of the text that he or she reads. And teaching Arabic could be use for four skill especially reading skill. Arabic teaching in reading skill can use reading text because it one method to identify the means where he stopped reading and it could use dialogue reading. And the teacher can use onther method for this theaching.